Penstabil Pelaksanaan Tegangan Kinerja Berbasis AVR (Automatic Voltage Regulator) Pada Sistem Eksitasi di PLTA Ir. H. Djuanda Jatiluhur - Rais, Arkaan; Santoso, Dian Budi; Lambada, Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2024)
the increasingly rapid development of technology, students are prepared to prepare themselves and deal with it, not only in the form of theory but also its application in the real world of work. Knowledge obtained in lectures will be of little use if it is not accompanied by active experience in the real world of work as well as the application of science and technology in the field of electrical engineering. Students really need provision of insight and knowledge of the world of work, so that there is this practical work. Students do not only know the theory but also know the practice directly. AVR (Automatic Voltage Regulator) is an electrical system that functions to maintain voltage at a certain value, maintain the stability of reactive power flow, maintain power factor stability, maintain the stability of the rotor angle, limit the generator so that it continues to operate in a safe area. The AVR function is executed automatically using the PID on the controller. AVR is a system that is very important in the process of generating electrical energy.